A Proposed Minimum Standard Set of Outcome Measures for Cataract Surgery. - Mahmud, I.; Kelley, T.; Stowell, C.; Haripriya, A.; Boman, A.; Kossler, I.; Morlet, Nigel; Pershing, S.; Pesudovs, K.; Goh, P.; Sparrow, J.; Lundström, M. (2015)
IMPORTANCE: Aligning outcome measures for cataract surgery, one of the most frequently performed procedures globally, may facilitate international comparisons that can drive improvements in the outcomes most meaningful to patients. OBJECTIVE: To propose a minimum standard set of outcome measures for cataract surgery that enables global comparisons. DESIGN, SETTING, AND PARTICIPANTS: A working group of international experts in cataract outcomes and registries was convened, along with a patient advocate, to agree on a consensus of outcome measures for cataract surgery. In a modified Delphi process, the group met regularly between November 10, 2012, and November 21, 2013, to discuss which outcomes to include in a standard set. Included factors were based on extant literature, existing registries, and the experience of group members. Similarly, a series of consensus discussions were held to determine a set of risk factors to be gathered for each patient. The final shortlist was compiled into a standard set. Analysis was performed from November 22, 2013, to April 5, 2014. MAIN OUTCOMES AND MEASURES: Development of a recommended standard set encompassing preoperative metrics including patient risk factors, intraoperative factors including surgical complications, and postoperative cataract surgery outcomes. RESULTS: The recommended standard set encompasses all patients treated for cataracts by 1 of 4 surgical approaches (phacoemulsification, sutured manual extracapsular cataract extraction, sutureless manual extracapsular cataract extraction, or intracapsular cataract extraction). The recommended metrics to be recorded preoperatively include demographics, ocular history and comorbidities, preoperative visual acuity, and patient-reported visual function. The recommended outcomes were split into intraoperative and postoperative metrics. Intraoperative outcomes include capsule-related problems, dislocation of lens nucleus fragments into the vitreous, and other complications. Postoperative outcomes include visual acuity, refractive error, patient-reported visual function, and early and late complications of surgery. The suggested follow-up for collection of postoperative outcomes is up to 3 months. CONCLUSIONS AND RELEVANCE: A minimum standard set of outcome measures for cataract surgery is important for meaningful comparison across contexts. The proposed data set is a compromise between all useful data and the practicalities of data collection.